Birth prevalence of orofacial cleft in a tertiary hospital in Riyadh, Saudi Arabia: A retrospective audit - Wasmiya A. AlHayyan; Samar Al Hayek; Sarah S. AlOtabi; Shahad A. AlGhanim (Elsevier, 2021)
Aim: The present study aimed to calculate the birth prevalence of orofacial cleft patients in King Abdulaziz Medical City (KAMC) Tertiary Care Hospital in Riyadh City, KSA. Material and methods: The data utilized in this retrospective study were obtained from the birth data registry at the hospital covering the period between January 2014 and December 2018. The data collected for the orofacial cleft patients pertained to the birth year, type of cleft, gender, and associated syndromes. Results: The total number of documented orofacial cleft cases born between 2014 and 2018 was 78, with a birth prevalence of 1.8 per 1000 live births and no gender bias. Cleft palate (CP) represented the most common type at 38.5% (n = 30), followed by cleft lip at 26.9% (n = 21) and unilateral cleft lip and palate at 24% (n = 19). The least common type was facial cleft, at 3.4% (n = 6). Syndrome association was seen in 15.4% (n = 12) of the cases. Conclusion: The birth prevalence of orofacial clefts in KAMC Riyadh city is in accordance with the worldwide ratio and similar to the birth prevalence reported in the Middle East area. CP showed more prevalence than the other orofacial cleft types, and the association with syndromes was significantly low.